MARGINALISASI GENDER DALAM PENGAMBILAN KEPUTUSAN (Studi Kualitatif Kaum Perempuan Di Lembaga Legislatif Kota Manado) - Alamona, Junaivan; Zakarias, John D.; Kawung, Eveline J. R. (Universitas Sam Ratulangi, 2017)
Gender discrimination have cause of misery and poverty for the especially for women that more often experience discrimination. Marginalization to gender for women is no longer an something new, but this has been a custom are indissoluble in the social life, national and state.One of a result of marginalisasi people women is, the decline in a contribution to and participation in government.The number of 16 (sixteenths) of the female as a member in the DPRD of Kota Manado, does not make up for the possibility of marginalization against women in the stage of decision-making, even though that is is not open, but over a of manner or of action / mannerisms and the system that done and it is not as a normal way of doing.Struggle to fulfill 30% of women who occupies a seat legislative it actually has a number of the purpose of pure, other than that the rights of women are given the necessary attention especially a woman right in the political field as a citizen who also have equal rights with men. Empowerment issues woman becomes the outline of the think about of the representation of women in politics, so that policies and laws which are arranged gender perspective, and of course it becomes a hope for a struggle which is quite long.Keywords: gender, legislative, discrimination